Rancang Bangun Aplikasi Pengolahan Dokumen Export Muatan Kapal Berbasis Web Pada PT Tresnamuda Sejati - Amalia, Rosi Nanda; Lemantara, Julianto; Nurcahyawati, Vivine (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
PT Tresnamuda Sejati or TMS is a company in the field of shipping. Currently, there is damage or loss of documents SI (Shipping Instruction) by 5% due to the shipper submit documents in paper form to be entered again by parts of the document. The impact of this, the shipper was disappointed with the service companies of having to send documents SI twice. In addition shipper can not monitor the status of cargo shipments and should call a customer service many times. In terms of managerial, at the end of the reporting process export activities already underway. Section only archives document and map the document manifest within a period of one month. The impact of this, the head of the company late in evaluating business processesTo solve these problems, the needed export document processing applications. This application will be made consisting of web-based shipping instruction data input features, status monitoring feature cargo shipments, and the end of the reporting features in graphical form.With this application, the shipper can make shipping instruction data input directly into the website, in addition to the shipper can also monitor the position / status of the current cargo being shipped to the port of destination. Head of the branch can also view reports in real time export activities.Â Â Kata Kunci : Shipping, Shipping Instruction, Information Systems Document Processing, Web-based